Years of discord American politics and society, 1961-1974 - Blum, John Morton 1921-2011. (New York W.W. Norton, 1991)
Focuses on the political history of the United States during the years 1961 to 1974.
UCASM-1452 (UCASM001452)
Includes bibliographical references (p. [485]-501) and index.
Keywords: United States -- Politics and government -- 1961-1963.; United States -- Politics and government -- 1963-1969.; United States -- Politics and government -- 1969-1974.